Challenges on New Normal EFL Teaching and Learning Process of ICT Integration: Summative Teachers’ Perception toward Formative Assessment - Rismayanti, Luh Ayu; Artini, Luh Putu; Utami, I.G.A Lokita Purnamika (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2024)
With the intentional goal of promoting the equality of technology literacy in the world, formative assessment acknowledged as one of alternative assessment in educational system in responses to the demands of new normal EFL teaching and learning process in which conveys potential advantages for an educational system. Formative assessment is interesting to be exposed cause it offers the use of assessment for learning as the guidance to find out as much as the learners do during the learning process. The perception of teachers toward the application of formative assessment is interesting to be exposed cause it offers challenges during the new normal EFL teaching and learning process. This writing attempted at describing summative teachers’ perception on the implementation of formative assessment which promotes differentiated instruction   opportunities   for   helping   students’   movement.   A qualitative approach with case study research design were carried out to seek out the writing’s objective. The preliminary data was attained through observation and the primary data was attained through interviews gathered from the summative teachers’ perception toward formative assessment practices. Results reveals positive perception toward the formative assessment practices during EFL teaching and learning process.